Enhancing Soil Microbial Communities in Sudan Savanna: Exploring the Impact of Cow Dung and Inorganic Fertilizer on Actinomycetes Population in Alfisol - Almu , Hamisu; Sani , Abdulkadir; Ahmad , Nasiru Abdulkadir (Emerging Issues in Agricultural Sciences Vol. 9, 2023)
The experiment was conducted to examine the actenomycetal populations under Dung and Inorganic Fertilizers in the Soil. . Cow Dung and Inorganic Fertilizer on Alfisol soil was laid down at Samaru for more than 60 years to determine whether the yield potential of tested crops could be maintained under continuous cultivation and the best combination of organic and inorganic fertilizers needed to achieve this. Ever increasing the demand for food has intensified the determination for Cow Dung and Inorganic fertilizers as pre-requisite for development. Hence, the impact of these to tremendous microbial communities in the Sudan Savanna. This study attempts to identify whether the influence of cow dung and inorganic fertilizer on population of actinomycetes, its effect and to maintain yield potential of tested crops under continuous cultivation. The experiment consisted of 4 treatments (Cow Dung, Nitrogen, Phosphorus, and Potassium) each at 3 levels (0, 1, and 2) applied annually in all possible combination. Each combination had one replicates only and there were 81 plots arranged in 9 blocks. The laboratory experiment involves an analytical study of the number of actinomycates in the soil as influence by organic and inorganic fertilizers. Generally, soil amendments have been found to affect actinomycates numbers to about 60% increased. Where phosphorus has been continuously applied at 2 and 1 levels, the actinomycetal counts were observed to be higher than where no amendments were made. The fertilization with N.P.K, particularly nitrogen in form of (NH4+)2 SO4 resulted in acidification of the soil and strong development of actinomycates. Actinomycates were found to help in the decomposition of organic matter in to humus and release of nitrogen. However, there is still much to be done in inorganic fertilizer on actinomycetal counts.